2019
DOI: 10.1007/s41030-019-00103-7
|View full text |Cite
|
Sign up to set email alerts
|

Can the Number of Radiofrequency Activations Predict Serious Adverse Events after Bronchial Thermoplasty? A Retrospective Case-Control Study

Abstract: Introduction: Bronchial thermoplasty (BT) is a bronchoscopic procedure that involves the delivery of thermal radiofrequency energy to the bronchial wall for treating severe asthma. It has been suggested that too many radiofrequency activations could induce serious adverse events (SAEs) at an early stage. We aimed to Enhanced digital features To view enhanced digital features for this article go to https://doi.org/10.6084/ m9.figshare.10043030.This study revealed that the number of radiofrequency activations is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Similar to the research conducted by Shota Yamamoto et al, 21 this study also revealed that baseline lung function [baseline FEV1 and baseline FEV1% predicted] might exert certain influence on BT activation number. Moreover, correlation and regression studies showed that total BT activations were not associated with clinical response to BT, except for a weak correlation ACQ improvement in the third BT session.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the research conducted by Shota Yamamoto et al, 21 this study also revealed that baseline lung function [baseline FEV1 and baseline FEV1% predicted] might exert certain influence on BT activation number. Moreover, correlation and regression studies showed that total BT activations were not associated with clinical response to BT, except for a weak correlation ACQ improvement in the third BT session.…”
Section: Discussionsupporting
confidence: 88%
“…However, in any study, the cumulative number of activations performed during 3 BT sessions was not associated with histological changes on bronchial biopsy (6). Some authors have proposed that the number of RF activations during BT is not associated with severe adverse events after BT (39). In contrast, others have concluded that an increased number of RF activations during BT results in a more significant number of serious adverse events.…”
Section: Problems and Prospectsmentioning
confidence: 70%
“…Yamamoto S. et al also revealed that increase in the number of radiofrequency activations during BT is related to a decrease in FEV 1 and %FEV 1 from baseline. The number of radiofrequency activations, however, is not associated with SAEs including pneumonia after BT [17]. The patient presented herein received a total of 294 effective activations which were more than the average activations in practice [13].…”
Section: Discussionmentioning
confidence: 90%